Mobility Device Use and Mobility Disability in U.S. Medicare Beneficiaries With and Without Cancer History - Bluethmann, Shirley M.; Flores, Eileen; Campbell, Grace; Klepin, Heidi D. (Journal of the American Geriatrics Society (JAGS), 2020)
BACKGROUND/OBJECTIVES To examine the prevalence of mobility device use in U.S. community‐dwelling older adults including older adults with cancer history (“survivors”) and to estimate mobility disability noting variation by cancer history, cancer site, and other factors to improve early detection of mobility limitations. DESIGN Cross‐sectional analysis from the 2011 National Health and Aging Trends Study. SETTING In‐person interviews in the homes of study participants. PARTICIPANTS Nationally representative sample of community‐dwelling Medicare beneficiaries, aged 65 and older (n = 6,080 including 1,203 survivors). MEASUREMENTS Participants were asked about cancer history, pain that limited activity, mobility device use (eg, canes, walkers, wheelchairs, and scooters), history of falls, and medical conditions plus they were assessed for approximate mobility disability using a 3‐m gait speed test. The results were scored on a scale of 0 to 4 (0 = lowest, 4 = highest) using criteria from the National Institute on Aging. RESULTS A total of 19% of older adults and 23% of survivors reported using one or more mobility device, most commonly a single‐point cane. Approximately 10% of breast, 6% of prostate, and 3% of colorectal cancer survivors reported using two or more devices in the past month. Survivors had lower mean gait speed scores (2.27) than adults without cancer history (2.39). In regression models, survivors were 18% less likely than adults without cancer history to score high on the gait speed test (odds ratio = .82; P < .05). Prior mobility device use, history of multiple falls, unhealthy weight, Black race, multimorbidity, and pain that limited activity were associated with lower gait speed scores in all participants (all P < .05). CONCLUSION A greater proportion of older survivors used mobility devices than adults without cancer history. Mobility device use varied by cancer site and was highest in survivors of breast, colorectal, and gynecological cancer. Survivors were also more likely to show signs of mobility disability, based on gait speed, compared with adults without cancer history. These indications, although modest, suggest that older survivors may require special attention to functional changes in survivorship.